2021
DOI: 10.48550/arxiv.2101.00331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of wall-modeled LES for external aerodynamics in the NASA Juncture Flow

Abstract: The use of computational fluid dynamics (CFD) for external aerodynamic applications has been a key tool for aircraft design in the modern aerospace industry. CFD methodologies with increasing functionality and performance have greatly improved our understanding and predictive capabilities of complex flows. These improvements suggest that Certification by Analysis (CbA) -prediction of the aerodynamic quantities of interest by numerical simulations (Clark et al. 2020) may soon be a reality. CbA is expected to na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previously, comparisons between surface streamlines of skin friction from the LES have been compared with experimental visualizations to qualitatively study the nature of the flow structures [20,22,34]. For this flow, Williams et al [55] performed clay-kerosene mixture based visualizations and observed a pair of counter-rotating vortices in the aft section of the bump.…”
Section: Meshmentioning
confidence: 99%
“…Previously, comparisons between surface streamlines of skin friction from the LES have been compared with experimental visualizations to qualitatively study the nature of the flow structures [20,22,34]. For this flow, Williams et al [55] performed clay-kerosene mixture based visualizations and observed a pair of counter-rotating vortices in the aft section of the bump.…”
Section: Meshmentioning
confidence: 99%